1990
DOI: 10.1021/bi00471a012
|View full text |Cite
|
Sign up to set email alerts
|

States of aggregation and phase transformations in mixtures of phosphatidylcholine and octyl glucoside

Abstract: The result of mixing varying concentrations of the nonionic detergent octyl glucoside (OG) with small unilamellar vesicles (SUV) of egg phosphatidylcholine (PC) made by sonication depends on the ratio between OG and PC in the mixed aggregates. When this molar ratio (Re) is lower than 1.4, the detergent partitions between the PC vesicles and the aqueous medium with a partition coefficient of K = 0.033 mM-1. As a consequence of introduction of OG into the bilayers, the vesicles grow in size. The resultant vesicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

42
159
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(201 citation statements)
references
References 41 publications
42
159
0
Order By: Relevance
“…It has been shown that the process of liposome formation is in many respects the reverse of solubilization [21], the latter being described by a three-stage model [22]. Interestingly, in a number of studies on the solubilization of liposomes by detergents, a maximum of the turbidity was measured at the intermediate stage [23,24], similar to the maximum of the ~.-curve in our experiments.…”
Section: Discussionsupporting
confidence: 85%
“…It has been shown that the process of liposome formation is in many respects the reverse of solubilization [21], the latter being described by a three-stage model [22]. Interestingly, in a number of studies on the solubilization of liposomes by detergents, a maximum of the turbidity was measured at the intermediate stage [23,24], similar to the maximum of the ~.-curve in our experiments.…”
Section: Discussionsupporting
confidence: 85%
“…Vesicle ↔ micelle transitions have been studied in some detail by turbidity measurements (7,8), nuclear magnetic resonance (8,9), and cryotransmission electron microscopy (10,11). These studies were generally performed with phosphatidylcholine (PC) as the phospholipid [often with PC from egg yolk, which contains 16:0 acyl chains at the sn -1 position and mainly unsaturated (18:1 Ͼ 18:2 Ͼ 20:4) acyl chains at the sn -2 position].…”
mentioning
confidence: 99%
“…This result agrees with those of a previous study by Almog et al showing that the liposome suspension was essentially vesicular within the upward turbidity curve in octylglucoside-EggPC system. 9) In the region of the downward turbidity curve, the EggPC content in the nonvesicular portion increased after centrifugation, defining the destruction of vesicles (data not shown).…”
Section: Discussionmentioning
confidence: 90%
“…In the past decades much attention has been paid to the interaction of detergents with phospholipid membranes. [9][10][11] Octylglucoside, Triton X100, and bile acid derivatives were most widely studied. [12][13][14] Although CHAPS has been widely used in membrane biology, little is known of the details of the interaction of CHAPS and vesicles.…”
mentioning
confidence: 99%